A study on climate change impacts on the built environment in Singapore - Lin, Yuanjie (2016)
Climate change on built environment has been a concern issue all over global. As construction of buildings plays a major part in Singapore industry, therefore it is necessary to look into the wind climate change impacts that could affect Singapore buildings. Wind load velocity alone will not affect the stability of the building and will not cause it to collapse. However, a component or façade of each building could fail and collapse onto the streets due to corrosion by the temperature, rain and wind load to cause the connection of the bolts and nuts to fall apart. The objective of this report is to study the wind climate in Singapore and its wind velocity pressure. Projected trend of wind speed in Singapore in 50 years will also be mentioned in this report. And an example calculation of wind load pressure acting on a simple building from Germany will be shown and it is based on Eurocode 1 on wind load with comparison made to Singapore National Annex. From the calculations, the basic wind velocity used from Germany example is higher than Singapore National Annex basic wind velocity. Therefore further studies could be done to increase Singapore National Annex basic wind velocity to match the projected trend wind speed in 50 years down the road.